Computational analysis of the aerothermodynamic effects in a reentry vehicle with surface discontinuity like a combined GAP/STEP - Paulo Henrique Mineiro Leite (2015)
This work is a computational study of a hypersonic rarefied non-reacting flow past a combined gap/step configuration at zero-degree angle of attack in thermal nonequilibrium conditions. Effects on the flowfield structure and on the aerodynamic surface quantities due to changes in the gap L/H ratio and on the step frontal-face height h in a combined gap/step configuration are investigated by employing the Direct Simulation Monte Carlo method. The work focuses the attention of designers of hypersonic configurations on the fundamental parameter of surface discontinuity, which can have an important impact on even initial design. The results presented highlight the sensitivity of the primary flowfield properties - velocity, density, pressure, and temperature -to changes in the gap L/H ratio and in the step frontal-face height h in a combined gap/step configuration. In addition, the behavior of heat transfer, pressure and skin friction coefficients due to variation in the gap L/H ratio and in the step frontal-face height h is detailed. For the conditions investigated in the present account, the analysis shows that hypersonic flow past a combined gap/step configuration in the transition flow regime is characterized by a strong compression ahead of a combined gap/step, which influences the aerodynamic surface properties upstream and adjacent to the step frontal-face. The analysis also shows that the upstream disturbance imposed by the combined gap/step configuration increased with increasing the step frontal-face height h. As a consequence, it was found that the aerodynamic heating and pressure loads were affected by the step frontal-face height changes. Locally high heating and pressure loads were observed at three locations along the surface, i.e., on the lower surface, on the frontal-face surface, and on the upper surface. It was evident that these loads increased with increasing the step frontal-face h. Peak values for the heat transfer coefficient on the frontal-face surface were at least one order of magnitude larger than the maximum value observed for a smooth surface, i.e., a flat-plate without a combined gap/step. Furthermore, the gap L/H ratio in a combined gap/step did not affect the aerodynamic surface coefficients along lower surface. Additionally, it was also found that density and pressure inside the gap in a combined gap/step configuration dramatically increased when compared to those observed for the gap alone due to the presence of the step. Finally, a comparison of the present simulation results with numerical and experimental data showed close agreement concerning to the wall pressure and kinetic temperature acting on the combined gap/step surface.